Integration of Social Media in Business: A Case of Nepal - Bhattrai, Ateeb (Nepalese Journal of Economics, 2025)
This study examines the integration of social media in business: A case of Nepal. Prosperity of the business is the dependent variable. The selected independent variables are online advertisements, online transaction options, online campaigns, updates on online trends and social media presence. The primary source of data is used to assess the opinion of respondents regarding online advertisements, online transaction options, online campaigns, updates on online trends, social media presence and prosperity of the business. The study is based on primary data of 138 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of the integration of social media in business: A case of Nepal. The study showed a positive impact of online advertisement on prosperity of the business. It indicates that effective online advertisements leads to higher prosperity of the business. Similarly, the study showed a positive impact of social media presence on prosperity of the business. It indicates that presence in social media attract customers that leads to increase in prosperity of the business. Likewise, the study showed a positive impact of online transaction options on prosperity of the business. It indicates that online transaction option is vital for convenience of consumers and prosperity of the business. Further, the study showed a positive impact of update on online trends on prosperity of the business. It indicates that online trends are one of the powerful marketing tools for today’s businesses. In addition, the study showed a positive impact of online campaigns on prosperity of the business. It indicates that online campaigns enhances the prosperity of a business.